A Qualitative Evaluation of Telemedicine Service Implementation in Morowali Regency, Indonesia - Gilvandris Aimang; Rajindra; Abdul Kadri; Irna Olvaliani Aimang (Ganesha Medicina, 2026)
Telemedicine has become an important strategy for improving healthcare delivery, especially in geographically challenged areas. In Morowali Regency, dispersed settlements and limited infrastructure hinder access to health services. This study evaluated telemedicine implementation based on clinical effectiveness, efficiency, accessibility, and user satisfaction. A descriptive qualitative study with purposive sampling was conducted at Morowali Regional General Hospital and five primary healthcare centers involving 15 informants, including managers, physicians, patients, and an IT operator. Data were collected through in-depth interviews, observation, and document review, then analyzed thematically using the Miles and Huberman interactive model supported by NVivo software. Four major themes emerged: clinical effectiveness, efficiency, accessibility, and user satisfaction. From the clinical effectiveness perspective, telemedicine facilitated clinical consultations, diagnostic support, and inter-facility coordination, although its use remained inconsistent and technically constrained. From the efficiency perspective, telemedicine reduced travel burden and improved access to specialist services for remote communities, but efficiency gains were limited by weak workflow integration. From the accessibility perspective, telemedicine expanded healthcare access despite infrastructure disparities and irregular service continuity. From the user satisfaction perspective, most healthcare providers and patients expressed positive experiences, although technical disruptions and the absence of structured evaluation mechanisms remained challenges. Overall, telemedicine showed benefits across all dimensions, highlighting the need for stronger infrastructure, routine utilization, and institutionalized evaluation to support sustainable and equitable healthcare delivery in geographically challenged regions.